Leader as priest: Plucking the fruit of a flawed metaphor. (May 2014) - Ruth, Damian
This paper takes its cue from Hatch et al. and their metaphor of leader as priest. This metaphor is extended in order to critically assess the importation of the discourse of spirituality into the arena of corporate leadership. In exploring this extended metaphor it becomes apparent that the concept of a spiritually informed corporate leadership is flawed. We may expect individuals to behave ethically and morally, but we should not confuse this with good or bad corporate leadership and link such leadership to corporate action. By pushing the limits of the leader-priest metaphor, we do not claim to vitiate the value of the metaphor, but we provide different perspectives on some standard questions and show that the problem of reprehensible corporate action might be more productively addressed as an issue of poor quality social and legal design rather than a spiritual or moral deficit.